Islamist Women of Hamas : Between Feminism and Nationalism - Islah Jad (Université de Provence, 2010)
In December, 1995,when Hamas announced the establishment of the Islamic National Salvation Party, a political organisation separate from its military wing, it opened the way for involvement of the Islamic movement in the political processes brought about in the West Bank and Gaza with the signing of the Oslo Accords and the arrival of the Palestinian National Authority. In speaking of the rights of different groups, including women, in its founding statement, and in setting up in Gaza a Women’s Action Department, the new Party opened its doors to the ‘new Islamic woman’ and to a significant evolution in Islamist gender ideology in Gaza, if not in the West Bank -- where, due to Hamas’ policy there of targeting only males, there exists no parallel to the Salvation Party or organisational support for women like that represented by the Women’s Action Department in Gaza. Hamas’ gender ideology, like that of the secularist parties, remains contradictory, and doors to women’s equality only partly open ; nevertheless, Islamist women have managed to build impressive, well-organised women’s constituencies among highly educated and professional women coming from poor and refugee backgrounds ; and the Salvation Party shows an increasing tendency to foster gender equality and more egalitarian social ideals, while holding fast to the agenda of national liberation. These advances have been achieved both through alternative interpretations of Islamic legal and religious texts, and through positive engagement with the discourses of other groups, whether secular feminists or nationalists. In contrast, secularists are losing ground by advocating a discourse of rights in isolation from the national agenda and in the absence of a mobilising organisation. These developments suggest possibilities for mutual accommodation between Islamist and other Palestinian groups. They suggest also that the nature of the state proposed by Islamists will depend to a large extent on the visions and challenges posed by other nationalist and secularist groups.